The Kashmir Case - Abdul Qayyum Khan (Rawalpindi NUST Press, 2013)
Autobiography and political memoirs of a well-known Kashmiri leader and freedom fighter.
Keywords: Revolutionaries -- Azad Kashmir -- Biography